Dietary inflammatory index and cardiometabolic risk in US adults. (September 2018) - Mazidi, Mohsen; Shivappa, Nitin; Wirth, Michael D.; Hebert, James R.; Mikhailidis, Dimitri P.; Kengne, Andre Pascal; Banach, Maciej
Abstract: Background and aims: We investigated the association between Dietary Inflammatory Index (DII ® ) scores and cardio-metabolic risk factors singly and in combination as metabolic syndrome (MetS). Methods: We used data from participants selected from the US National Health and Nutrition Examination Survey (NHANES). Analyses were restricted to participants with data available on dietary intake, biochemical data, and anthropometric measurements from 2005 to 2012. Statistical analyses used the SPSS ® Complex Samples v22.0 (IBM Corp, Armonk, NY) and accounted for the survey design and sample weights. Energy-adjusted-DII (E-DII ® ) expressed per 1000 kcal was calculated from 24-h dietary recalls. Of the 17, 689 participants with evaluable data, 8607 (48.3%) were men. The mean age was 45.8 years in the overall sample, with men being slightly younger than women (44.9 vs. 46.5 years, p  = 0.05). Results: In multivariable-adjusted regression models, the odds of MetS, its components, as well as obesity, and elevated high-sensitivity C-reactive protein (hsCRP) increased across increasing quartiles of E-DII ( p < 0.001). In age, sex, race, income-to-poverty ratio-adjusted models, these and other cardiovascular disease risk factors (triglycerides/high density lipoprotein cholesterol (HDL-C) ratio, apolipoprotein (B) and HbA1C) increased across quartiles of the E-DII (all p < 0.001), while HDL-C levels decreased ( p < 0.001). Conclusions: This study suggests associations between MetS, its components, subclinical inflammation, and the DII. These results reinforce the view that diet plays an important role in the occurrence of cardiovascular diseases. Highlights: We investigated the association of cardio-metabolic risk factors, singly or in combination, and inflammatory markers with dietary inflammatory index (DII ® ) scores. Our results indicate that adjusted levels of cardio-metabolic risk factors significantly increased (decreased for HDL-cholesterol) across increasing quartiles of DII score. The prevalence of metabolic syndrome, obesity, elevated high sensitivity C-reactive protein and glucose intolerance increased with increasing inflammatory potential of diet.